2013
DOI: 10.1002/mabi.201300057
|View full text |Cite
|
Sign up to set email alerts
|

A Core Cross-Linked Polymeric Micellar Platium(IV) Prodrug with Enhanced Anticancer Efficiency

Abstract: A core cross-linked polymeric micellar cisplatin(IV) conjugate prodrug is prepared by attaching the cisplatin(IV) to mPEG-b-PLL biodegradable copolymers to form micellar nanoparticles that can disintegrate to release the active anticancer agent cisplatin(II) in a mild reducing environment. Moreover, in vitro studies show that this cisplatin(IV) conjugate prodrug displays enhanced cytotoxicity against HepG2 cancer cells compared with cisplatin(II). Further studies demonstrate that the high cellular uptake and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…The cellular localization studies indicated anisamide targeting ligand conjugation enhanced cellular uptake and promoted cell apoptosis. In the pancreatic cancer mouse xenograft model, the pegylated and anisamide‐targeted PSQ NPs showed drastically superior efficacy to oxaliplatin in inhibiting tumor growth . In a similar study, folic acid (FA) targeted platinum (IV)‐conjugated NaYF 4 :Yb 3+ /Er 3+ NPs were prepared for targeted drug delivery and cell imaging .…”
Section: Platinum (Iv) Complex‐based Delivery Systemsmentioning
confidence: 98%
See 2 more Smart Citations
“…The cellular localization studies indicated anisamide targeting ligand conjugation enhanced cellular uptake and promoted cell apoptosis. In the pancreatic cancer mouse xenograft model, the pegylated and anisamide‐targeted PSQ NPs showed drastically superior efficacy to oxaliplatin in inhibiting tumor growth . In a similar study, folic acid (FA) targeted platinum (IV)‐conjugated NaYF 4 :Yb 3+ /Er 3+ NPs were prepared for targeted drug delivery and cell imaging .…”
Section: Platinum (Iv) Complex‐based Delivery Systemsmentioning
confidence: 98%
“…Furthermore, NPs can be specifically targeted to cancer cells by surface functionalization with affinity ligand to further enhance the accumulation of NPs within tumor cells . Polysilsesquioxane (PSQ) was composed of siloxane networks with organic or metal‐organic bridging ligands . The [dachPtSi] monomer containing Pt (IV) complex was used to prepare PSQ NPs, and the surface of PSQ NPs was further engineered with PEG or anisamide ligand.…”
Section: Platinum (Iv) Complex‐based Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionalized platinum nanoparticles have shown size- and shape-dependent specific and selective therapeutic properties [64, 67, 80]. In many cases, platinum nanoparticles containing other organic substances have also been used as pro-drug [67, 70, 81].…”
Section: Reviewmentioning
confidence: 99%
“…Functionalized platinum nanoparticles have shown size- and shape-dependent specific and selective therapeutic properties [64, 67, 80]. In many cases, platinum nanoparticles containing other organic substances have also been used as pro-drug [67, 70, 81]. Manikandan et al [82] have shown that small platinum nanoparticles (5–6 nm) are biocompatible and exhibit apoptosis-inducing properties [49, 83].…”
Section: Reviewmentioning
confidence: 99%